2019
DOI: 10.3390/molecules24213856
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Stability of Oil Body Emulsions from Diverse Plant Seeds Using Sodium Alginate

Abstract: In this study, peanut, sesame, and rapeseed oil bodies (OBs) were extracted by the aqueous medium method. The surface protein composition, microstructure, average particle size d4, 3, ζ-potential of the extracted OBs in aqueous emulsion were characterized. The stability of the OB emulsions was investigated. It was found that different OB emulsions contained different types and contents of endogenous and exogenous proteins. Aggregation at low pHs (<6) and creaming at high pHs (7 and 8) both occurred for all of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Two salts (NaCl and CaCl2) affect the emulsion stability and were observed using experiment and simulation by Zhong et al [20] and Zhang et al [47]. Despite this, we investigated the influence of salt on the stability of W/O and O/W microemulsion by the DPD simulation shown in Figure 7.…”
Section: Influence Of Inorganic Salt On the W/o And O/w Microemulsion...mentioning
confidence: 99%
“…Two salts (NaCl and CaCl2) affect the emulsion stability and were observed using experiment and simulation by Zhong et al [20] and Zhang et al [47]. Despite this, we investigated the influence of salt on the stability of W/O and O/W microemulsion by the DPD simulation shown in Figure 7.…”
Section: Influence Of Inorganic Salt On the W/o And O/w Microemulsion...mentioning
confidence: 99%
“…According to Stokes formula, the increase of viscosity can increase the drag force exerted on the droplets and reduce their creaming rates in the emulsion (Zhao, 2008). Zhang et al (2019) found that low concentrations of sodium alginate (0.30–0.45 wt%) could stabilize the 1 wt% peanut, sesame, and rapeseed OBs emulsions below the isoelectric point of the OBs through electrostatic interaction. While high concentrations of sodium alginate (1.2–1.5 wt%) improved the OBs emulsions stability through the viscosity effect at pH 7.0.…”
Section: Composition and Structure Of Obsmentioning
confidence: 99%
“…The peanut OB emulsions with oil content of 10% (w/w) were prepared by dispersing the OB cream into PBS (50 mM, pH 7), and then magnetic stirring for 30 min. 40,42 Droplet size and size distribution of the peanut OB emulsions were determined with the aid of a laser light scattering instrument (Malvern Mastersizer 2000, UK). The refractive index of dispersed phase and continuous phase was 1.47 and 1.33, respectively.…”
Section: Emulsion Preparation and Characterizationmentioning
confidence: 99%